A 150-168 GHz Mixer and Quadrupler Unit in SiGe BiCMOS Technology for JCAS Applications Based on DDS Signal Generation Up to 5 GHz - Isbilen, Timur; Breun, Sascha; Arneth, Nils; Schrotz, Albert-Marcel; Scheller, Kai; Franchi, Norman; Weigel, Robert (2025 IEEE Wireless and Microwave Technology Conference (WAMICON), 2025)
This paper presents a fully integrated mixer and quadrupler unit with a 3 dB bandwidth from 150 to 168 GHz and a maximum output power of -15 dBm. The circuit is designed for JCAS applications focusing on the up-conversion of arbitrary ramp sequences (e.g., for FMCW radar) generated by a commercial DDS block. The unit comprises a polyphase filter, LO buffer amplifiers, a double-balanced single-sideband mixer, and a subsequent frequency quadrupler, which provides a bandwidth extension by a factor of four. Thus, 18 GHz of bandwidth in the D-band can be achieved by using a 4.5 GHz DDS signal source. The proposed arrangement is optimized for low phase noise, high spurious-free dynamic range (SFDR), and compatibility with various communication applications. An SFDR exceeding 24dBc is maintained across the entire measured RF frequency range (150 to 168 GHz), with suppression of spurs greater than 30 dBc observed in the 156 to 164 GHz range. The circuit was fabricated using a 90 nm SiGe BiCMOS technology with ft/fmax of 300GHz/500GHz, respectively, and has a power consumption of 175 m
Keywords: direct digital synthesis; FMCW radar; D-band; joint communication and sensing; single-sideband mixer; frequency quadrupler; SiGe BiCMOS